DAMPAK KULIAH KEWIRAUSAHAAN TERHADAP SIKAP DAN MOTIVASI MAHASISWA DALAM BERWIRAUSAHA - Fitriani, Dyah (Optimum: Jurnal Ekonomi dan Pembangunan, 2014)
This study analyze the effect of studentsâ perceptions to the attitudes and motivations to become entrepreneurs. In addition, this study also analyze the infl uence of the advantages of entrepreneurship and entrepreneurial barriers to student interest in entrepreneurship. The sample was students who have taken courses in Entrepreneurship Management Department. The sampling technique used was purposive random sampling. Partial least square (PLS) used to analyze data.The results of this study were 1) there is a signifi cant effect between perception and benefi ts of entrepreneurship to entrepreneurship motivation, 2) there is no signifi cant effect between studentsâ perceptions of the attitudes to entrepreneurship, 3) there is no signifi cant effect between entrepreneurship constraints on entrepreneurship motivation, and 4) there is a signifi cant effect between motivation towards entrepreneurship attitude.